2019
DOI: 10.1007/s00127-019-01769-9
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial working conditions and depressive disorder: disentangling effects of job control from socioeconomic status using a life-course approach

Abstract: Purpose Job control, the combination of skill discretion and decision authority, is considered a central component of the psychosocial working environment. This longitudinal study examines the relation between job control and risk of incident depressive disorder using a life-course approach. Methods We analyze data from The Danish Work Life Course Cohort study, including all Danish individuals aged 15–30 who entered the Danish labor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 84 publications
(91 reference statements)
0
21
0
1
Order By: Relevance
“…Of the nine studies, four were related to employment conditions, capturing contract type and working hours [34][35][36][37]. The five remaining studies captured concepts relevant to psychosocial workplace exposures including workplace sexual harassment [38,39], psychosocial job quality [40], work stressors [41], and job control [42].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the nine studies, four were related to employment conditions, capturing contract type and working hours [34][35][36][37]. The five remaining studies captured concepts relevant to psychosocial workplace exposures including workplace sexual harassment [38,39], psychosocial job quality [40], work stressors [41], and job control [42].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Of the remaining six, one was from France [34], one from Canada [35], one from Turkey [36], one from Egypt [37], one from Australia [40], and one from Denmark. [42] Three studies used a cross-sectional design [34,36,38], while the remaining six used prospective cohorts and employed a longitudinal design. [35,37,[39][40][41][42] Descriptive information related to the studies is shown in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, one study based on the DaWCo population, examining the association between job control and depressive disorder has been published 26. The study found an association between job control and subsequent depressive disorder, after adjustment for possible confounding by SES, measured in a life-course perspective.…”
Section: Findings To Datementioning
confidence: 99%
“…Considering the above-delineated evidence for an association between adverse working conditions and the risk of developing mental disorders (3)(4)(5)(6)(7)(8)(9)(10)(11)(12) and the ongoing discussion about using work matched to one's "knowledge, skills and circumstances, and undertaken in a safe, healthy and supportive working environment" (13) as a therapeutic tool for individuals with prevalent mental health problems and disorders (13,(15)(16)(17), it is disconcerting that organizational-level, work environment interventions to protect or enhance workers' mental health seem either not to qualify for systematic reviews (18,20) or, if they do, show rather weak or inconsistent results (26,27).…”
mentioning
confidence: 99%